Transfer The Effect Of Muscle Training (Fixed-Moving) From The Healthy Part To Rehabilitate The Femoral Muscle - Alattabi, Sameerah Abdulrassol; Abdul Hameed, Suhad Haseeb (International Journal of Psychosocial Rehabilitation, 2020)
The problem lies in the injury of the rectus femoral muscle partial rupture in some men and women non-athletes, which led the researcher to pay attention to this situation and use in the rehabilitation side associated with skeletal muscles and the musculoskeletal system and thinking in a manner that accelerates and prevents the occurrence of muscular atrophy resulting from not moving for a long time. The objectives of the research were to prepare fixed exercise for the injured part and fixed and mobile exercise for the proper part . And to identify the impact of muscle exercise stomach and the transfer of training to rehabilitate the injured part of the rectus femoral muscle in term of the range of motor and muscle strength. While the hypotheses of the research showed the presence of statistically significant differences in the transfer of the impact of fixed and mobile muscular training to qualify the rectus femoral muscle in terms of muscle strength and motor range between the pre and post tests of the sample and in favor of the post test. The researcher used the experimental method and the main experiment sample consisted of 16 patients with partial rupture of the rectus femurs muscle, and the results were treated statistically to show the differences between the pre-and post tests after the use of the prepared exercises. The effect of training, which led to the improvement of strength and motor range as the researcher recommended the use of fixed and mobile exercises and transfer the impact of training for other injuries.